"Here you have to face the real China!": International students' experiences at a Chinese superdiverse university. (2021) - Yuan, Mei; Sude, Bilige; Chen, Ning; Dervin, Fred
Highlights: Uses superdiversity to examine international Chinese higher education. Focuses on the understudied case of an ethnic-group serving institution. International students' experiences of superdiversity appear to be limited. Yet students' knowledge and awareness of Minzu superdiversity is compelling. Recommendations are made for superdiversity and interculturality in study abroad. Abstract: Using the concept and approach of superdiversity, this paper complements current studies on the internationalization of higher education by focusing on the understudied case of an ethnic-group serving institution in China. 17 international students at this superdiverse institution, where members of the 56 Chinese 'ethnic' Minzu groups live and study together, were interviewed about their experiences in Chinese and English. Considering the originality and complexity of this specific Chinese context, the authors chose Dialogic Discourse Analysis to analyse the data. This complex analytical method allows to identify and problematise the ways superdiversity seems to have influenced (or not) the students' stay in China and their engagement with Minzu. Although superdiversity is reported as a pull factor for most students, their experiences of it and encounters with members of different Minzu groups, appear to be limited. However, the students' knowledge and awareness of this important aspect of Chinese society is compelling when the students discuss what they have learnt interculturally. They also seem to have modified many of their essentialist and culturalist representations of China. The article ends with recommendations for both scholars and Ethnic group-serving institutions in China and elsewhere, for rethinking intercultural experiences in study abroad.